The State of Sustainable Markets 2023 - International Trade Centre (United Nations, 2024)
The International Trade Centre has teamed up once again with the Research Institute of Organic Agriculture and the International Institute for Sustainable Development to provide data about 14 major sustainability standards for bananas, cocoa, coffee, cotton, oil palm, soybeans, sugarcane, tea and forestry products. This year’s report adds data from 2021 and finds that slow growth resumed after a dip in 2020. The publication helps shape decisions of policymakers, producers and businesses, working to address systemic labour and environmental challenges through certified sustainable production.